Configuration of the values of Mary, before and after the violation, in Satan by Mario Mendoza - González Rallón, Jéssica Ivón Renata (Rastros Rostros, 2020)
Introduction: this text addresses the novel Satan, by Mario Mendoza. This novel will present a semiotic analysis of one of his characters called Maria, who, a root of a personal catastrophe, has a change in his axiological system that marks a before and after in his life. Methodology: this analysis of the configuration of the values before and after the catastrophic event is carried out through an interpretive-generative tour in favor of the Inter-Semiotic School of Paris. It will passthrough figurative structures, narrative, thematic and actantial structures, and elementary semantic structures. Conclusions: it is intended to find, in a broader sense, the reasons why you can motivate the achievement of quick and easy money, revenge, honor, repentance and claiming your dignity along with your goodpractices as he had been taught since childhood.
Keywords: semiotics; identity; violation